Molecular dynamics simulation of crosslinking process and mechanical properties of epoxy under the accelerator. Issue 2 (11th November 2022) - Chen, Fengjun; Liu, Fan; Du, Xiaogang
Abstract: To simulate the crosslinking process of epoxy resin under the accelerator action, the crosslinking system of bisphenol‐A diglycidyl ether (DGEBA) as a monomer, methyl tetrahydro‐phthalic anhydride (MTHPA) as a thermal curing agent and 2, 4, 6‐tris (dimethylaminomethyl) phenol (DMP‐30) as a thermal curing accelerator has been studied using molecular dynamics (MD) simulation. An algorithm that can construct the high‐crosslinked system with different crosslinking density is completed based on the Perl language, and the subsequent properties are simulated. The results of molecular dynamics simulation show that modulus have an increasing trend, and glass transition temperature (Tg) raises from 325 K to 480 K when crosslinking density is from 0% to 95.5%. Conversely, cohesive energy density lessens from 620 J/cm 3 to 170 J/cm 3, solubility and Poisson's ratio decrease, and the tensile strength firstly increases and then diminishes. The friction coefficient decreases firstly and then increases, meanwhile, the temperature suddenly adds by 20 K and the relative concentration distribution (RCD) grows by 1.58 times at the contact surface. This study predicts for the crosslinking process and micro mechanical properties in the DGEBA/MTHPA/DMP‐30 system. Abstract : A method of automatic crosslinking based on molecular dynamics is proposed for epoxy resin under accelerator. The physical and mechanical properties are simulated about the models of different crosslinking density. The friction simulation between the models and the copper surface was realized. This study has a certain prediction for the research of the crosslinking process and mechanical properties.